Acute haemorrhagic diarrhoea syndrome in dogs: 108 cases. (13th June 2015) - Mortier, F.; Strohmeyer, K.; Hartmann, K.; Unterer, S.
Abstract : No prospective studies including large numbers of dogs with acute haemorrhagic diarrhoea syndrome (AHDS) are published so far. The aim of this case–control study was to describe signalment, history, clinical signs, laboratory values and course of disease in dogs with AHDS. Dogs (108) with idiopathic acute haemorrhagic diarrhoea (<3 days) were prospectively enrolled. Clinical assessment was performed by calculation of the 'AHDS index' (0–18). The hospital population and 21 healthy dogs served as control groups. Dogs with AHDS had a significantly lower body weight (median 9.8 kg) and age (median five years) than other dogs of the hospital population (20 kg; 10 years) (P<0.001). Predisposed breeds were Yorkshire terrier, miniature pinscher, miniature schnauzer and Maltese. The syndrome was more likely to occur during winter. Vomiting preceded the onset of bloody diarrhoea in 80 per cent of dogs and haematemesis was observed in half of those cases. Median AHDS index at presentation was 12 (range 3–17). Haematocrit was generally high (median 57.1 per cent; range 33–76 per cent), but exceeded 60 per cent only in 31.4 per cent of dogs. Haematocrit of 48.1 per cent of dogs was above reference range, as was monocyte (50.0 per cent), segmented (59.6 per cent) and band neutrophil count (45.2 per cent). A rapid clinical improvement occurred during the first 48 hours.